2, 3-Ethylene-bridged dihomooxacalix[4]arenes: synthesis, X-ray crystal structures and highly selective binding properties with anions. (29th May 2018) - An, Lin; Wang, Jia-wei; Wang, Chan; Zhou, Shan-shan; Sun, Jing; Yan, Chao-Guo
Abstract : Three novel 2, 3-ethylene-bridged p-tert -butyldihomooxacalix[4]arenes3a–3c were selectively synthesized by direct O -alkylation of p-tert -butyldihomooxacalix[4]arene1 with excess of 1, 2-dibromoethane in controlled basic systems. Abstract : Three novel 2, 3-ethylene-bridged p-tert -butyldihomooxacalix[4]arenes3a–3c were selectively synthesized by direct O -alkylation of p-tert -butyldihomooxacalix[4]arene1 with excess of 1, 2-dibromoethane in controlled basic systems. Their corresponding conformational features were clearly elucidated by 1 H NMR spectra and single crystal structures. Their binding abilities toward a variety of anions (SO4 2−, SO3 2−, CO3 2−, HSO3 −, HCO3 −, NO3 −, CH3 COO −, Br −, I − and Cl − ) have been assessed (3a was taken for example) and compared to those afforded with the unconstrained p-tert -butyldihomooxacalix[4]arene1 and the analogous 1, 3-di-(2-bromoethyl) substituted calix[4]arene derivative4 by determining the fluorescence titrations. The results showed that 2, 3-ethylene-bridged dihomooxacalix[4]arene3a has the most significant selectivity and high affinity for I − . In contrast, p-tert -butyldihomooxacalix[4]arene1 can mainly bind most anions (SO3 2−, CO3 2−, HCO3 −, NO3 −, and I − ), but has a poor selectivity preference. The analogous4 exhibits only a weak binding ability for I −, which suggests that 2, 3-ethylene-bridged p-tert -butyl-dihomooxacalix[4]arene3a would be useful in the design of new selective supramolecular receptors for anions.